Neonatal Platelets Are Less Reactive than Adult Platelets to Physiological Agonists in Whole Blood - Rajasekhar, Damodara; Kestin, Anita S; Bednarek, Francis J; Ellis, Patricia A; Barnard, Marc R; Michelson, Alan D (Thrombosis and Haemostasis, 1994)
Previous studies have reported that the platelets of healthy term neonates have either diminished or normal reactivity compared to the platelets of adults. To circumvent the methodologic problems of previous studies, we used a whole blood flow cytometric method to study neonatal platelet reactivity to thrombin, a combination of ADP and epinephrine, and U46619 (a stable thromboxane A2 analogue). Inclusion in the assay of the peptide GPRP (an inhibitor of fibrin polymerization) enabled us to study platelet reactivity to human α-thrombin in whole blood. Umbilical cord blood and day 1 peripheral blood were collected from 30 healthy term neonates and compared to peripheral blood from 20 normal adults. In whole blood samples without added agonist, there were no significant differences between neonates and adults in the platelet binding of monoclonal antibodies 6D1 (GPIb-specific) or 7E3 (GPIIb-IIIa complex-specific). As determined by S12 (a P-selectin-specific monoclonal antibody), neither neonates nor adults had circulating degranulated platelets. However, in both cord and peripheral whole blood samples, neonatal platelets were significantly less reactive than adult platelets to thrombin, ADP/epinephrine, and U46619, as determined by the extent of increase in the platelet surface expression of P-selectin and the GPIIb-IIIa complex, and the extent of decrease in the platelet surface expression of the GPIb-IX complex. For example, as compared to maximal platelet surface P-selectin in adults (with thrombin 10 U/ml), thrombin 1 U/ml resulted in platelet surface P-selectin of 95 ± 2% (mean ± S.E.M.) in adult peripheral blood, but only 70 ± 4% in cord blood and 70 ± 3% in neonatal peripheral blood (p <0.0001). Thrombin 0.1 U/ml resulted in platelet surface P-selectin of 49 ± 4% in adult peripheral blood, but only 10 ± 2% in cord blood and 17 ± 2% in neonatal peripheral blood (p α0.0001). Similar results were obtained in a washed platelet system. In summary: 1) Compared to adult controls, neonatal platelets are hyporeactive to thrombin, a combination of ADP and epinephrine, and a thromboxane A2 analogue in the physiologic milieu of whole blood. 2) The hyporeactivity of neonatal platelets compared to adult platelets is the result of a defect intrinsic to neonatal platelets. 3) Whole blood flow cytometry is particularly advantageous for neonatal studies because only 5 μl of blood per assay is required.